Rekomendasi Pemupukan P Untuk Tanaman Jagung Pada Tanah Inceptisols Menggunakan Pendekatan Uji Tanah - . Syafruddin (UNIVERSITY OF LAMPUNG, 2008)
Productivity of maize in Central Sulawesi has been significantly low. The evidence has been a challenge on maize development in this area. Rational fertilization based on soil conditions and nutrient requirement of plants croped, has saved use of fertilizer, increased efficiency of the farm and also reduced negative impacts of chemical fertilizer. This will sustain the use of land resource. The researceh aimed to establish phosphorus fertilizer recomendation for maize crops at several levels of soil nutrients status in dryland rationally and spesicific location. The research was conducted in for stages i.e.: (1) survey on nutrient status, (2) calibration test and correlation study, (3) availability class determination of P and (4) composting P fertilizer recomendation. Split plot design was used. Main plot was soil nutrients status, consisting of 4 levels and sub plot was fertilizer dosage consisting of 5 levels, with 3 replications. The size of each plot was 4 m x 5 m. The results showed that the treatments applied indicated an interaction. Nutrient availability class and plant responses were divided by tree classes i.e: low, medium and high level with extraction methods (reagents) that excellently correlate, are Trough, Colwell and Bray 1 methods. Optimun dosage of P fertilizer for treatment were, 76 kg P2 O5 ha -1 for low nutrient status 41 kg P2 O5 ha -1 for medium nutrient status and high nutrient status to nutrient status very high, P fertilizer was not required.